Creation, physical and chemical properties of alkil-2-((5-phenethyl-4-R-1,2,4- triazole-3-yl)thio)acet(propan,benz)imidates - Ignatova, T. V.; Kaplaushenko, A.; Nagornaya, N.; Avramenko, A.; Ігнатова, Тетяна Вікторівна; Каплаушенко, Андрій Григорович; Нагорна, Наталія Олександрівна; Авраменко, Антоніна Іванівна (My University, 2019)
Objective: The aim of this research was to synthesize and evaluate physical-chemical properties of 5-pheneyhyl-4-R-3-thio-1,2,4-triazole and to establish identity and structure of the synthesized compounds, namely alkil-2-((5-phenethyl-4-R-1,2,4-triazole-3-yl)thio)acet(propan,benz)imidates. Methods: As starting materials for synthesis of alkil-2-((5-phenethyl-4-R-1,2,4-triazole-3-yl)thio)acet(propan,benz)imidates, the corresponding 2-((5-phenethyl-4-R-1,2,4-triazole-3-yl)thio)aceto(propane,benzo)nitrile have been used. Synthesis has been set in the absolute alcohol medium (propanol or butanol alcohol) with chloroform, using the saturation with dry hydrogen chloride. Results: In this study, we have developed nine new compounds have been received as a result of synthetic transformations, the structure of synthesized compounds has been confirmed by modern complex of physical-chemical methods of analysis (1H NMR-spectroscopy, elemental analysis), and their individuality has been conducted on gas-liquid chromatograph Agilent 1260 Infinity HPLC equipped with a mass spectrometer Agilent 6120. Conclusion: As a result of the work, it was synthesized the new compounds of the series of alkil-2-((5-phenethyl-4-R-1,2,4-triazole-3-yl)thio) acet(propan,benz)imidates and was characterized by elemental analysis and proton nuclear magnetic resonance spectroscopic analysis.
Keywords: 1,2,4-Triazole; Synthesis; Physical and chemical properties